Child protection practitioners: Including children in decision making. Issue 3 (28th February 2018) - Woodman, Elise; Roche, Steven; McArthur, Morag; Moore, Tim
Abstract: This article presents findings from a study with 467 child protection practitioners in Australia to determine their practice responses and views on children's participation. The practitioners, recruited from 5 state jurisdictions, completed an online survey responding to case studies designed to determine the extent to which they would seek and include children's perspectives in decision making, and their confidence in talking to children. We report on practitioners' responses to a case study of a 5‐year‐old girl with suspicious bruising where the mother reports domestic violence. Based on previous research, it was hypothesized that the child's young age would lead to low levels of confidence in consulting with the child and giving weight to her perspective. In contrast to the findings of other research, our results show that almost all workers report that they would speak with the child, would be confident doing so, and would give weight to the child's perspective. Our discussion explores the potential reasons for the difference in these findings compared with other research, including the experience of practitioners, increased child‐centred policy in Australia, multiple understandings of participation, and variation in children and practitioner views of participation.